2018
DOI: 10.1074/jbc.ra118.003021
|View full text |Cite
|
Sign up to set email alerts
|

Usp25m protease regulates ubiquitin-like processing of TUG proteins to control GLUT4 glucose transporter translocation in adipocytes

Abstract: Insulin stimulates the exocytic translocation of specialized vesicles in adipocytes, which inserts GLUT4 glucose transporters into the plasma membrane to enhance glucose uptake. Previous results support a model in which TUG (ether containing a BX domain forLUT4) proteins trap these GLUT4 storage vesicles at the Golgi matrix and in which insulin triggers endoproteolytic cleavage of TUG to translocate GLUT4. Here, we identify the muscle splice form of Usp25 (Usp25m) as a protease required for insulin-stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(81 citation statements)
references
References 72 publications
8
73
0
Order By: Relevance
“…We previously found that the N‐terminal domain (NTD) of USP1 generated by autocleavage is removed by KLHDC2 (Lin et al , 2018). Comparably to USP1, the FAU, SDE2, and TUG proteins contain an ubiquitin‐like (UBL) domain with the characteristic C‐terminal diGly motif and all these proteins are processed by deubiquitinating enzymes (Dubs) (Olvera & Wool, 1993; Habtemichael et al , 2018; Thakran et al , 2018). Dubs‐mediated cleavage results in their UBL‐harboring NTD fragments ending with a diGly tail (Fig 7A; Olvera & Wool, 1993; Jo et al , 2016; Habtemichael et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that the N‐terminal domain (NTD) of USP1 generated by autocleavage is removed by KLHDC2 (Lin et al , 2018). Comparably to USP1, the FAU, SDE2, and TUG proteins contain an ubiquitin‐like (UBL) domain with the characteristic C‐terminal diGly motif and all these proteins are processed by deubiquitinating enzymes (Dubs) (Olvera & Wool, 1993; Habtemichael et al , 2018; Thakran et al , 2018). Dubs‐mediated cleavage results in their UBL‐harboring NTD fragments ending with a diGly tail (Fig 7A; Olvera & Wool, 1993; Jo et al , 2016; Habtemichael et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Comparably to USP1, the FAU, SDE2, and TUG proteins contain an ubiquitin‐like (UBL) domain with the characteristic C‐terminal diGly motif and all these proteins are processed by deubiquitinating enzymes (Dubs) (Olvera & Wool, 1993; Habtemichael et al , 2018; Thakran et al , 2018). Dubs‐mediated cleavage results in their UBL‐harboring NTD fragments ending with a diGly tail (Fig 7A; Olvera & Wool, 1993; Jo et al , 2016; Habtemichael et al , 2018). Therefore, we tested the hypothesis that the diGly/C‐degron KLHDC2 pathway eliminates Dubs cleavage products.…”
Section: Resultsmentioning
confidence: 99%
“…Clathrin heavy chain-22 is particularly interesting because it is expressed in humans but not in rodents. Additionally, TUG and TC10 have been implicated in GLUT4 exocytosis (58,59). Detailed analysis of in vivo models is required to fully understand the role of all these proteins in regulating metabolism.…”
Section: The Glut4 Itinerary and Its Many Unknownsmentioning
confidence: 99%
“…Although this had previously been considered exclusively as a post-Golgi process, more recent data make clear that recycled GLUT4 accumulates in a pool of small (∼50 nm diameter) vesicles that reside near the ERGIC and cis -Golgi compartments, in association with TUG, Golgin-160, and ACBD3 (Acyl-CoA Binding domain-containing protein 3, also known as GCP60) (Xu et al, 2011; Bogan, 2012; Orme and Bogan, 2012; Belman et al, 2015). Upon insulin stimulation, these vesicles are mobilized by TUG cleavage, and they are proposed to traffic to the cell surface by an unconventional secretion pathway that bypasses the Golgi stack (Xu et al, 2011; Bogan, 2012; Habtemichael et al, 2018). GLUT4 is S-acylated and the PAT responsible for this modification was recently identified (Du et al, 2017).…”
Section: Additional Examples For Anterograde Routing Of S-acylated Mementioning
confidence: 99%
“…Data also suggest that the accumulation of a pool of small, insulin-responsive vesicles may be impaired during the development of type 2 diabetes, which may result from excess membrane diacylglycerols and sphingolipids (Garvey et al, 1998; Maianu et al, 2001; Czech, 2017; Habtemichael et al, 2018; Petersen and Shulman, 2018). We speculate that these excess lipids might potentially disrupt the palmitoylation-based sorting mechanisms discussed above and thus contribute to attenuated insulin action.…”
Section: S-palmitoylation Confers Membrane Proteins a “Sorting-competmentioning
confidence: 99%